Abnormal enhancement of light output by cation mixing in ZnxMg₁₋ₓWO₄ nanocrystals - Tupitsyna, I.A.; Maksimchuk, P.O.; Yakubovskaya, A.G.; Dubovik, A.M.; Seminko, V.V.; Zvereva, V.S.; Trubaeva, O.G.; Hubenko, K.O.; Vovk, O.M.; Malyukin, Y.V. (Functional Materials, 2017)
In the paper the effect of light output increase with maximum at x = 0.5 observed previously for the mixed ZnxMg₁₋ₓWO₄ crystals is demonstrated for nanocrystals with the same composition. The enhancement of light output up to 3 times at the transition from bulk to nanosize was shown. This effect is determined by nonlinear dependence of concentration of oxygen vacancies with minimum at x = 0.5 for ZnxMg₁₋ₓWO₄ nanocrystals."